2020
DOI: 10.1093/sleep/zsaa045
|View full text |Cite
|
Sign up to set email alerts
|

Detecting sleep using heart rate and motion data from multisensor consumer-grade wearables, relative to wrist actigraphy and polysomnography

Abstract: Study Objectives Multisensor wearable consumer devices allowing the collection of multiple data sources, such as heart rate and motion, for the evaluation of sleep in the home environment, are increasingly ubiquitous. However, the validity of such devices for sleep assessment has not been directly compared to alternatives such as wrist actigraphy or polysomnography (PSG). Methods Eight participants each completed four nights … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
67
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 116 publications
(75 citation statements)
references
References 47 publications
4
67
0
1
Order By: Relevance
“…Previous validation studies involving the Oura ring showed that it performs comparably with research-grade actigraphs, over single nights of study in predominantly Caucasian participants. 19 , 20 As prior work suggests that age, BMI, biological sex, skin tone and hair follicle density are important factors when it comes to accuracy and generalizability of wearable studies based on HR and motion sensors, it is important to consider these factors and assess replicability in an East Asian sample. 21 , 22 …”
Section: Introductionmentioning
confidence: 99%
“…Previous validation studies involving the Oura ring showed that it performs comparably with research-grade actigraphs, over single nights of study in predominantly Caucasian participants. 19 , 20 As prior work suggests that age, BMI, biological sex, skin tone and hair follicle density are important factors when it comes to accuracy and generalizability of wearable studies based on HR and motion sensors, it is important to consider these factors and assess replicability in an East Asian sample. 21 , 22 …”
Section: Introductionmentioning
confidence: 99%
“…rPPG-based devices can extract cardiorespiratory parameters, such as heart rate variability (HRV) and surrogates of respiratory activity 13 15 . They have been shown to be able to assess sleep architecture in healthy and disordered populations 16 19 . As such, they constitute an attractive candidate for objective unobtrusive OSA monitoring.…”
Section: Introductionmentioning
confidence: 99%
“…With current advancements in technology and in particular in wearable devices, more attention is being taken toward using wearables to assess circadian and ultradian rhythms in humans (reviewed in [ 67 ]). A major advantage of using wearables is that they enable real-time and high-resolution monitoring of one’s circadian rhythms by tracking physiological indications (e.g., heart-rate, rest-activity, sleep, glucose, skin temperature and exposure to external cues such as light) [ 68 , 69 , 70 , 71 ]. The data obtained from one or multiple wearables can serve as high-dimensional input data to computational models or machine learning approaches in order to personalize chronotherapy for patients [ 72 ].…”
Section: Clinical Overviewmentioning
confidence: 99%